Analisa Efektivitas Komunikasi Pemasaran Produk Aqua Menggunakan Customer Response Index Melalui Kegiatan Promosi - Akmaludin, Akmaludin (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2012)
Promotion is crystallization of a form of marketing communication, modern marketing communication should be able to communicate the brand or Its products to consumers in an integrated way, so consumers will know more about the benefits of the product. To find products that are marketed to consumers, certainly needs to be measured in evaluating how much the strength of the product is received by consumers. Many methods are used in determine level of effectiveness of communication conducted as Customer Decision Model (CDM), EPIC Model, Direct Rating Method (DRM), and Customer Response Index (CRI).Custormer Response Index (CRI) is one that often used in the measurement of the effectiveness of marketing communications products. Variables used to measure the effectiveness of marketing communication consists of five variables including Awareness, Comphrehend, Interest, Intention, and Action. In connection with the acquisition value is performed with CRI can be seen from the results of recent advertising campaigns through the media. If the CRI points earned exceeds 50% or more, then said to the effectiveness of marketing communications well worth it. For the research results through media advertisements broadcast television advertising products aqua value of marketing communications effectiveness gets 59% of acquisition value, this means that the measurement of the effectiveness of marketing communications products using the method Custormer Response Index (CRI) produces assessments that can be said to be good. With reference to the acquisition of data, can be seen how much the consumer is not how much consumer response and the response, it was said as a response index.